Program Animasi Interaktif Pengenalan Kebudayaan Indonesia - Febriawan, Arvelian Chris; Siregar, Juarni; Cahyadi, Cepi (LPPM STMIK ANTAR BANGSA, 2018)
Abstract— The current education system can not be separated from the use of information technology in the learning process, especially for elementary school students. The introduction of culture to elementary school students today tends to use only theoretical methods such as using books and blackboards, so the learning process is less interesting because of the monotony While the number of foreign cultures that enter in Indonesia increasingly threatens Indonesian culture to disappear or claimed by the State lan. By beginning to introduce Indonesian culture to children in elementary school, they have basic reference about the outline of the cultures that exist in Indonesia.Therefore, it takes an interactive learning media about the introduction of Indonesian culture for elementary school students. It is expected that with this interactive animated learning media can improve the motivation of learning elementary school students about Culture in Indonesia and eliminate the boredom of monotonous Learning activities. Intisari—Sistem pendidikan saat ini tidak terlepas dari penggunaan teknologi informasi dalam proses pembelajaran terutama untuk siswa-siswi sekolah Dasar. Pengenalan kebudayaan pada siswa SD saat ini cenderung menggunakan metode teoritis saja seperti menggunakan buku dan papan tulis, sehingga proses belajar kurang menarik karena monoton Sementara banyaknya budaya asing yang masuk di Indonesia semakin mengancam kebudayaan Indonesia menjadi menghilang ataupun diklaim oleh Negara lan. Dengan mulai mengenalkan budaya Indonesia pada anak di bangku sekolah dasar, mereka mempunyai acuan dasar tentang gambaran secara garis besar budaya-budaya yang terdapat di Indonesia.Oleh karena itu dibutuhkan media pembelajaran yang interaktif tentang pengenalan kebudayaan Indonesia bagi siswa-siswi SD. Diharapkan dengan adanya media pembelajaran Animasi interaktif ini dapat meningkatkan motivasi belajar siswa-siswi SD tentang Kebudayaan yang ada di Indonesia serta menghilangkan rasa bosan terhadap aktivitas Belajar yang monoton. Kata Kunci—Animasi, Interaktif, Budaya, Media, Pengenalan, Teknologi